Comparison of optimal drop heights in 2 drop-jump exercises for basketball athletes with differing strength levels - Yue, L; Liu, Z; Wang, S; Lin, T; Liang, C; Yin, J; Liu, C. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Previous research has primarily focused on bounce drop jump (BDJ) rather than countermovement drop jump (CDJ) in studying optimal drop heights for drop jump. This study explored the biomechanic parameters of both BDJ and CDJ and their relationship with performance across varying drop heights based on the percentage of squat-jump height (SJH).